The Sexualized Girl: A Within‐Gender Stereotype Among Elementary School Children. Issue 5 (17th August 2015) - Stone, Ellen A.; Brown, Christia Spears; Jewell, Jennifer A.
<x xml:space="preserve">Abstract</x> Two studies (conducted in 2013) examined whether elementary‐aged children endorse a within‐gender stereotype about sexualized girls. In Study 1, children (N = 208) ages 6–11 rated sexualized girls as more popular but less intelligent, athletic, and nice compared to nonsexualized girls. These distinctions were stronger for girls and older children, and in accordance with our developmental intergroup theoretical framework, were related to children's cognitive development and media exposure. Study 2 (N = 155) replicated the previous findings using more ecologically valid and realistic images of girls and further explored individual differences in the endorsement of the sexualized girl stereotype. Additional results indicated that the belief that girls should be appearance focused predicted their endorsement of the sexualized girl stereotype.